Motivasi Masyarakat Desa Mire Terhadap Perlindungan Hutan Di Kawasan Hutan Lindung Kecamatan Ulubongka Kabupaten tojo una-una - Septian Rulianto; Adam Malik; Andi Sahri Alam (Jurnal Warta Rimba, 2018)
Population growth around the protected forest will increase the threat damage caused by uncontrolled land clearing which can damage the ecosystem environment. This study aimed to know people motivation in Mire Village, Ulubongka Sub-district, Tojo Una-Una Regency of protected forest area. Method of this study was qualitative descriptive, through collecting primary and secondary data. Both of these data were obtained from interview result with the respondent and some supporting data such as village government and literature study. Data analysis used Likert Scale 5-3-1, to find out how far community motivation toward protection forest in protected forest area in Mire. The result of this study indicated that ecological motivation is still quite dominant with a percentage (98,82%) by being in the motivated category compared with economic motivation by (62,35%) and social motivation (97,84%) in relation to regional safeguards of protected forest area in Mire. Ecology motivation is encouraged by the strong desire of people in Mire to preserve its forest area, including the preservation and ecosystem stability that will be maintained in the future. In an effort to protect the forest in Mire, people do replanting of critical lands and establishing village regulations along with the strict punishments for people violate the rules. Keywords: People Motivation, Protection Forest